2008
DOI: 10.1099/mic.0.2008/016782-0
|View full text |Cite
|
Sign up to set email alerts
|

The coiled-coil protein-binding motif in Fusarium verticillioides Fsr1 is essential for maize stalk rot virulence

Abstract: Fusarium verticillioides (Sacc.) Nirenberg (teleomorph Gibberella moniliformis Wineland) is one of the key pathogens of maize stalk rot disease. However, a clear understanding of stalk rot pathogenesis is still lacking. Previously, we identified the F. verticillioides FSR1 gene, which plays a key role in fungal virulence and sexual mating. The predicted Fsr1 protein contains multiple protein-binding domains, namely a caveolin-binding domain, a coiled-coil structure, and a calmodulin-binding motif at the N term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In line with the revelation by Yamamura & Shim (2008) in fungal pathogens, we have shown the possible link between pioneer gene-mediated M. incognita pathogenesis and CWDE activities using RNAi, which is perhaps the only effective technique to study gene manipulation in plant-parasitic nematodes. Remarkably, our experiments revealed that induced suppression of one parasitism gene may cause overexpression or suppression of another group of parasitism genes.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In line with the revelation by Yamamura & Shim (2008) in fungal pathogens, we have shown the possible link between pioneer gene-mediated M. incognita pathogenesis and CWDE activities using RNAi, which is perhaps the only effective technique to study gene manipulation in plant-parasitic nematodes. Remarkably, our experiments revealed that induced suppression of one parasitism gene may cause overexpression or suppression of another group of parasitism genes.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, characterisation of the individual and integrative function of different nematode effectors is required for deeper understanding of plant-nematode interaction, which is as yet an underexplored territory. Interestingly, Yamamura & Shim (2008) showed that the coiled-coil domain of FSR1 gene plays a key role in the pathogenicity of the fungi, Fusarium verticillioides. Along with that, a potential link between FSR1-mediated virulence and activity of the fungal CWDEs (α-amylase, pectinase and cellulase) was also established.…”
mentioning
confidence: 99%
“…F. verticillioides defective for Fsr1 display reduced radial growth on agar, fewer aerial mycelia, and inability to penetrate and grow in maize stalk in a stalk-rot assay (Shim et al, 2006, Yamamura and Shim, 2008). While Fsr1 is not critical for male fertility in F. verticillioides , it is required for female fertility and the development of perithecia (Shim et al, 2006).…”
Section: Composition and Function Of Striatin Family Complexesmentioning
confidence: 99%
“…Similarly, deletion of Fsr1 in F. graminearu also leads to a block in perithecia development and significantly reduced head blight symptoms of this fungus on barley (Shim et al, 2006). In F. verticillioides , the growth and virulence defects of a ΔFsr1 strain could be rescued by expression of an Fsr1 mutant lacking the WD-repeat domain or by expression of a mutant lacking both the WD-repeat domain and the caveolin-binding domain (Yamamura and Shim, 2008). Given the importance of the WD-repeats for Mob3 binding in mammalian cells (Gordon et al, 2011), it will be interesting to determine if the F. verticillioides Mob3 homolog is dispensable for virulence.…”
Section: Composition and Function Of Striatin Family Complexesmentioning
confidence: 99%
See 1 more Smart Citation